The first species of Embioptera (Insecta) from the archipelago of Fernando de Noronha (Pernambuco: Brazil) - Costa-Pinto, Paula J.; Olivier, Renan S.; Rafael, José A. (Zootaxa, 2021)
Pararhagadochir is a South American genus of Archembiidae that can be identified by its anterior margin of submentum strongly concave, caudal process of the 10th left hemitergite forked, with internal tip seemingly a hook and the external tip a flat lobe, both tips always shorter than the width of 10th left hemitergite. Six species are recorded in Brazil, being distributed in all regions. In this work, Pararhagadochir noronhensis sp. nov. is described from the archipelago of Fernando de Noronha, Brazil.